A Wideband Annular Ring Radiator with Polygonal Ground Plane - Sucharita, Ch. V. S. Alekhya; Sneha, K.; Sastry, Neti Narasimha (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Vivaldi radiators and its variants have been extensively used for wideband single antenna and array applications. The Vivaldi radiator and other radiators such as spirals, log periodic, ridged gap wave guides are predominantly 3D antennas. There has been a need for a truly planar antenna for antenna array applications in the Communications, EW and Radar band of 6-18 GHz. In this paper a wideband radiator covering 6-22GHz is designed and analyzed using HFSS simulations. The popularly known UWB antenna technology is now quite matured leading to effective coverage of the communication band of frequencies from 3.1 to 10.6 GHz. This technology is adapted to design, analyze and implement a planar element radiator for array applications covering the 6-18GHz band. The antenna is realized in hardware with a return loss of less than -10dB over 7.2GHz to 22 GHz and good radiation patterns from 6.0 to 15 GHz.